E(x)=(x+1)²+(x-1)²-(x-2)(x+2)
Calculati E(1)+E(√2)
Ajotor !!!
Răspunsuri la întrebare
Răspuns de
2
E(x)=x²+2x+1+x²-2x-1-x²-2x+2x+2=
=x²+3
E(1)+E(√2)=(1)²+3+√2²+3=1+6+2=9
=x²+3
E(1)+E(√2)=(1)²+3+√2²+3=1+6+2=9
amadalin54:
E gresit
Răspuns de
0
e(*)=*2+2*+1+*2-2*-1-*-2-2*+2*+2
=*2+3
e(1)+e(2)=(1)2+3+22+3=1+6+2=9
=*2+3
e(1)+e(2)=(1)2+3+22+3=1+6+2=9
Alte întrebări interesante
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Istorie,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
10 ani în urmă
Franceza,
10 ani în urmă
Limba română,
10 ani în urmă